2014
DOI: 10.4088/pcc.13r01554
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Vilazodone, Serotonin, and Major Depressive Disorder

Abstract: Objective: To review the mechanism of selective serotonin reuptake inhibitor (SSRI)–mediated serotonergic neurotransmission, focusing on serotonin 1A (5-HT1A) autoreceptors, which are proposed to be involved in delaying therapeutic efficacy. Vilazodone was specifically designed to function both as an SSRI and a partial agonist at 5-HT1A receptors. This combined mechanism is proposed to decrease time to efficacy, minimize sexual side effects, and provide concomitant anxiolytic properties.Data Sources: A PubMed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 73 publications
0
15
0
1
Order By: Relevance
“…In this case, vilazodone is a partial agonist of the serotonin 5-HT 1A receptor in addition to being a potent serotonin reuptake inhibitor. [12] Approved by the US Food and Drug Administration (FDA) in 2011, the efficacy of vilazodone was demonstrated in a pair of double-blind, placebo controlled, randomized clinical trials (RCTs). [13,14] As these trials did not include an active comparator, no assessments of relative efficacy were possible.…”
Section: Market Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, vilazodone is a partial agonist of the serotonin 5-HT 1A receptor in addition to being a potent serotonin reuptake inhibitor. [12] Approved by the US Food and Drug Administration (FDA) in 2011, the efficacy of vilazodone was demonstrated in a pair of double-blind, placebo controlled, randomized clinical trials (RCTs). [13,14] As these trials did not include an active comparator, no assessments of relative efficacy were possible.…”
Section: Market Reviewmentioning
confidence: 99%
“…[12] A pooled analysis of the impact of vilazodone therapy on the symptoms of anxiety associated with MDD demonstrated that the drug's effect on anxiety symptoms was comparable to its effect on core depressive symptoms. [15] Of course, head-tohead trials are necessary to confirm that this effect differs from that of SSRIs or SNRIs.The RCTs of vilazodone have used structured scales to collect information on sexual adverse effects and found the rates of these effects to be only marginally greater than placebo.…”
Section: Market Reviewmentioning
confidence: 99%
“…In addition to functioning as an SSRI, vilazodone acts as a 5-HT1A receptor partial agonist, similar to buspirone. Preclinical studies show that activation of presynaptic 5-HT1A autoreceptors function to delay the anti-anxiety and antidepressant effects of SSRIs (34). Through simultaneous blockade of the SERT and activation of the 5-HT1A receptor, vilazodone may overcome this delay.…”
Section: Competitive Environmentmentioning
confidence: 99%
“…Through simultaneous blockade of the SERT and activation of the 5-HT1A receptor, vilazodone may overcome this delay. This dual mechanism of action can potentially shorten the delay of anti-depressive action, decrease side-effects related to serotonin reuptake inhibition in SSRI, and alleviate anxiety symptoms (35). The true clinical implications of this pharmacodynamics profile, however, remains unclear.…”
Section: Competitive Environmentmentioning
confidence: 99%
“…The monoamine theory, which has been the most widely accepted over recent decades, ascribed depression to an insufficient amount of serotonin and norepinephrine in the synapses located in the dorsal raphe nuclei and locus coeruleus, respectively. Serotonin neurotransmission is crucial in contributing to several important brain functions that are responsible for regulating mood, fear response, sleep, appetite and sexual behavior (Pierz & Thase, ). Norepinephrine signaling plays a vital role in coordinating neuronal network excitability and connectivity, as well as modulating behavior response and adaptation, while its deficiency leads to decreased alertness, low energy, stress, working memory impairment and problems in attention, concentration, motivation and cognition (Moret & Briley, ; O'Donnell, Zeppenfeld, McConnell, Pena, & Nedergaard, ).…”
Section: Introductionmentioning
confidence: 99%